ANALISA PERBANDINGAN PENGGUNAAN BIODIESEL DAN SOLAR TERHADAP UJI PRESTASI MESIN DIESEL ISUZU 120 PS - Aryananta Lufti; Harjanto, Budi; Silitonga, Frangky (PPM Sdirjianbang Akademi Militer, 2024)
To support teaching and learning activities at Akmil, many diesel-engined trucks are needed that use diesel. Considering that diesel is not a renewable resource, biodiesel is a more environmentally friendly alternative, because it is produced from vegetable or animal oil. Testing the performance of diesel engines with biodiesel and diesel at various speeds shows differences, although not significant. This can be used as a guideline in selecting fuel, especially for TNI AD vehicles, and it is hoped that biodiesel can be widely known as an alternative fuel.